Patterns of lexis in the research article genre: a contrastive study of lexical priming in English, Portuguese and Japanese - Aragão, Rodrigo Moura Lima de (2023)
Lexical priming is a lexicon-oriented theory formulated by the British linguist Michael Hoey that assumes that previous experiences with language prepare or prime language users to communicate in one or another way. Everyone\'s mind is seen as a natural, complex concordance program that continuously associates words, sounds, and even syllables with a wide variety of linguistic resources and contextual factors, from individual words to genres, domains, and situations. According to the theory, psychological priming–an associative process–would be the main force behind a given language\'s typical form. Different languages are expected to exhibit different patterns of lexis as a result of their users\' particular associations and experiences, meaning that the mapping of patterns from one language to another would not result in standard language use in the target language. This dissertation attempts to contribute to the body of research on linguistic evidence for psychological priming by means of an investigation of research articles (RAs) in English, Portuguese, and Japanese. Using a collection of 240 RAs from 10 journals in Pediatrics and Management, several corpora and subcorpora were manually built to answer the following research questions: (1) To what extent is there evidence for genre-specificity related to psychological priming in RAs? (2) To what extent is there evidence for domain-specificity (disciplinary variation) related to psychological priming in RAs? (3) To what extent is there evidence for text-positional association related to psychological priming in RAs? (4) Do users of different languages make similar associations with semantically equivalent words in comparable contexts? With the aid of corpus analysis software programs, four research stages were carried out, each of which focused on a different question. In the first stage, specialized, single-genre corpora were compared with general, multi-genre reference corpora to extract RA-specific keywords. Highly typical keywords could be found, of which nine were selected. Collocates and semantic sets of the selected keywords were then contrasted. As a result, typical collocations and semantic associations were observed in the RA data. In the second stage, Pediatrics corpora were compared with Management corpora to extract both discipline-specific and non-discipline-specific keywords. Extremely typical as well as shared, common keywords were found; six non-discipline-specific keywords were then selected. Collocates and semantic sets of the selected keywords were contrasted, revealing distinguishing collocations and semantic associations for each discipline. In the third stage, the textual position of 18 selected discipline-specific keywords and the position of 2-4-word clusters containing the selected keywords were investigated across RA section subcorpora. While the clusters exhibited stronger textual colligational inclination, most of the keywords do not appear to be primed for use in specific parts of RAs. In the final stage, semantically equivalent, high-frequency nouns were searched in the English, Portuguese, and Japanese data. Textual position, collocates, and grammatical functions of seven selected words were then compared. As a result, textual colligations, collocations, and colligations of English and Portuguese nouns proved to be closer to each other; the associations of Japanese nouns exhibited more distinguishing features. Collectively, the findings provide strong support for Hoey\'s claims concerning both genre- and domain-specificity and add new layers of understanding to the existing knowledge about text-positional association and cross-linguistic variation. In addition to the theoretical contribution, the findings can be useful to (foreign) language teaching and learning for academic purposes and to academic translation as well.